Carriage Depot for the Maintenance of Passenger Cars Vchd-2 - Nurmukhamedov, Tolaniddin Ramziddinovich (European Journal of Life Safety and Stability (2660-9630), 2022)
The carriage depot for servicing passenger cars of JSC “Uztemiryulyulovchi" is considered. The main structural units of the car depot, which includes several departments, are marked. The stages of repair and equipment work of mobile units after their arrival at the depot are given.